Evaluation of the theoretical practical domain of the natural approach as an alternative strategy to facilitate the learning of the english language for the students of the eighth, ninth and tenth year of basic education of Colegio Nacional “Nueve de Octubre” of cantón Machala provincia de El Oro during the academic year 2013-2014. - Zambrano Ochoa, Ángel Alfredo (2014)
In January 2014 (diario el Telégrafo, January 28th2014) issued the results of the third edition of the EF EPI study (English Proficiency Index or index of the level of English), which was directed to more than 750,000 people over 18 years old, including students and employees. Unfortunately, Ecuador was ranked in the place 48 with a score of 46.90 over 100, with the lowest level of English among 60 countries of the world. These figures show that while our country's population increases there are fewer people investing their resources in learning this language. In order to deter such situation the National Government through the Ministry of Education started the implementation of measures such as: design, validate, and socialize the new curriculum of English, aligned to the Common European Framework of Reference for Languages (CEFR), to be able to tender new English textbooks paired to the new curriculum, and distribute them at no cost; to establish and apply the new guidelines of evaluation (with standardized tests) in the English language to work for state schoolsfor both applicants to become teachers and appointed teachersof English and establish a system of continuous training of English teachers to ensure the sustainability of the project.